salim-barzani

210 Reputation

3 Badges

0 years, 195 days

MaplePrimes Activity


These are questions asked by salim-barzani

there is must be a problem but i didn't figure out ?  in this command didn't give me my parameter why?
vars1 := indets(eqs1);
ans := solve(eqs1, {a[0], a[1], a[2], a[3], a[4], e[1], k[1], n[1], p[1]});

parameter.mw


 

restart

_local(gamma)

Warning, A new binding for the name `gamma` has been created. The global instance of this name is still accessible using the :- prefix, :-`gamma`.  See ?protect for details.

 

with(plots)

NULL

sol3 := sqrt(2)*sqrt(-tau*gamma)*tanh(x-tau*t^alpha/alpha)*exp(I*gamma*(x+((2*gamma^3*tau-4*gamma*tau+8*tau^2)/(2*gamma^2)-tau*gamma)*t^alpha/((gamma-2*tau)*alpha)))/gamma

NULL

lprint(indets(sol3, name))

{alpha, gamma, t, tau, x}

 

NULL

P :=   [ alpha=1, gamma=-2,  tau=3]

[alpha = 1, gamma = -2, tau = 3]

(1)

PP := convert(sol3, polar)

polar(2^(1/2)*abs(tau*gamma)^(1/2)*exp(-Im(gamma*(x+((1/2)*(2*gamma^3*tau-4*gamma*tau+8*tau^2)/gamma^2-tau*gamma)*t^alpha/((gamma-2*tau)*alpha))))*abs(tanh(x-tau*t^alpha/alpha)/gamma), argument((-tau*gamma)^(1/2)*tanh(x-tau*t^alpha/alpha)*exp(I*gamma*(x+((1/2)*(2*gamma^3*tau-4*gamma*tau+8*tau^2)/gamma^2-tau*gamma)*t^alpha/((gamma-2*tau)*alpha)))/gamma))

(2)

polarplot(sol3, x = -20 .. 20, t = 0 .. 10, axis[radial] = [color = "Blue"])

NULL

Download polar.mw

How i can find parameter after substitution in our pde 

restart

with(PDEtools)

with(LinearAlgebra)

NULL

with(SolveTools)

undeclare(prime)

`There is no more prime differentiation variable; all derivatives will be displayed as indexed functions`

(1)

declare(u(x, t))

u(x, t)*`will now be displayed as`*u

(2)

declare(f(x, t))

f(x, t)*`will now be displayed as`*f

(3)

pde := diff(u(x, t), `$`(x, 3))+6*u(x, t)*(diff(u(x, t), x))+diff(u(x, t), t) = 0

diff(diff(diff(u(x, t), x), x), x)+6*u(x, t)*(diff(u(x, t), x))+diff(u(x, t), t) = 0

(4)

map(int, diff(diff(diff(u(x, t), x), x), x)+6*u(x, t)*(diff(u(x, t), x))+diff(u(x, t), t) = 0, x)

3*u(x, t)^2+diff(diff(u(x, t), x), x)+int(diff(u(x, t), t), x) = 0

(5)

pde1 := %

3*u(x, t)^2+diff(diff(u(x, t), x), x)+int(diff(u(x, t), t), x) = 0

(6)

Y := u(x, t) = 2*(diff(ln(f(x, t)), `$`(x, 2)))

u(x, t) = 2*(diff(diff(f(x, t), x), x))/f(x, t)-2*(diff(f(x, t), x))^2/f(x, t)^2

(7)

L := eval(pde1, Y)

3*(2*(diff(diff(f(x, t), x), x))/f(x, t)-2*(diff(f(x, t), x))^2/f(x, t)^2)^2+2*(diff(diff(diff(diff(f(x, t), x), x), x), x))/f(x, t)-8*(diff(diff(diff(f(x, t), x), x), x))*(diff(f(x, t), x))/f(x, t)^2+24*(diff(diff(f(x, t), x), x))*(diff(f(x, t), x))^2/f(x, t)^3-6*(diff(diff(f(x, t), x), x))^2/f(x, t)^2-12*(diff(f(x, t), x))^4/f(x, t)^4-2*(diff(f(x, t), x))*(diff(f(x, t), t))/f(x, t)^2+2*(diff(diff(f(x, t), t), x))/f(x, t) = 0

(8)

numer(lhs(3*(2*(diff(diff(f(x, t), x), x))/f(x, t)-2*(diff(f(x, t), x))^2/f(x, t)^2)^2+2*(diff(diff(diff(diff(f(x, t), x), x), x), x))/f(x, t)-8*(diff(diff(diff(f(x, t), x), x), x))*(diff(f(x, t), x))/f(x, t)^2+24*(diff(diff(f(x, t), x), x))*(diff(f(x, t), x))^2/f(x, t)^3-6*(diff(diff(f(x, t), x), x))^2/f(x, t)^2-12*(diff(f(x, t), x))^4/f(x, t)^4-2*(diff(f(x, t), x))*(diff(f(x, t), t))/f(x, t)^2+2*(diff(diff(f(x, t), t), x))/f(x, t) = 0))*denom(rhs(3*(2*(diff(diff(f(x, t), x), x))/f(x, t)-2*(diff(f(x, t), x))^2/f(x, t)^2)^2+2*(diff(diff(diff(diff(f(x, t), x), x), x), x))/f(x, t)-8*(diff(diff(diff(f(x, t), x), x), x))*(diff(f(x, t), x))/f(x, t)^2+24*(diff(diff(f(x, t), x), x))*(diff(f(x, t), x))^2/f(x, t)^3-6*(diff(diff(f(x, t), x), x))^2/f(x, t)^2-12*(diff(f(x, t), x))^4/f(x, t)^4-2*(diff(f(x, t), x))*(diff(f(x, t), t))/f(x, t)^2+2*(diff(diff(f(x, t), t), x))/f(x, t) = 0)) = numer(rhs(3*(2*(diff(diff(f(x, t), x), x))/f(x, t)-2*(diff(f(x, t), x))^2/f(x, t)^2)^2+2*(diff(diff(diff(diff(f(x, t), x), x), x), x))/f(x, t)-8*(diff(diff(diff(f(x, t), x), x), x))*(diff(f(x, t), x))/f(x, t)^2+24*(diff(diff(f(x, t), x), x))*(diff(f(x, t), x))^2/f(x, t)^3-6*(diff(diff(f(x, t), x), x))^2/f(x, t)^2-12*(diff(f(x, t), x))^4/f(x, t)^4-2*(diff(f(x, t), x))*(diff(f(x, t), t))/f(x, t)^2+2*(diff(diff(f(x, t), t), x))/f(x, t) = 0))*denom(lhs(3*(2*(diff(diff(f(x, t), x), x))/f(x, t)-2*(diff(f(x, t), x))^2/f(x, t)^2)^2+2*(diff(diff(diff(diff(f(x, t), x), x), x), x))/f(x, t)-8*(diff(diff(diff(f(x, t), x), x), x))*(diff(f(x, t), x))/f(x, t)^2+24*(diff(diff(f(x, t), x), x))*(diff(f(x, t), x))^2/f(x, t)^3-6*(diff(diff(f(x, t), x), x))^2/f(x, t)^2-12*(diff(f(x, t), x))^4/f(x, t)^4-2*(diff(f(x, t), x))*(diff(f(x, t), t))/f(x, t)^2+2*(diff(diff(f(x, t), t), x))/f(x, t) = 0))

2*f(x, t)^2*(3*(diff(diff(f(x, t), x), x))^2+f(x, t)*(diff(diff(diff(diff(f(x, t), x), x), x), x))+f(x, t)*(diff(diff(f(x, t), t), x))-4*(diff(diff(diff(f(x, t), x), x), x))*(diff(f(x, t), x))-(diff(f(x, t), x))*(diff(f(x, t), t))) = 0

(9)

PP := simplify(2*f(x, t)^2*(3*(diff(diff(f(x, t), x), x))^2+f(x, t)*(diff(diff(diff(diff(f(x, t), x), x), x), x))+f(x, t)*(diff(diff(f(x, t), t), x))-4*(diff(diff(diff(f(x, t), x), x), x))*(diff(f(x, t), x))-(diff(f(x, t), x))*(diff(f(x, t), t))) = 0)

2*f(x, t)^2*(3*(diff(diff(f(x, t), x), x))^2+f(x, t)*(diff(diff(diff(diff(f(x, t), x), x), x), x))+f(x, t)*(diff(diff(f(x, t), t), x))-4*(diff(diff(diff(f(x, t), x), x), x))*(diff(f(x, t), x))-(diff(f(x, t), x))*(diff(f(x, t), t))) = 0

(10)

%/(2*f(x, t)^2)

3*(diff(diff(f(x, t), x), x))^2+f(x, t)*(diff(diff(diff(diff(f(x, t), x), x), x), x))+f(x, t)*(diff(diff(f(x, t), t), x))-4*(diff(diff(diff(f(x, t), x), x), x))*(diff(f(x, t), x))-(diff(f(x, t), x))*(diff(f(x, t), t)) = 0

(11)

collect(%, f)

(diff(diff(diff(diff(f(x, t), x), x), x), x)+diff(diff(f(x, t), t), x))*f(x, t)+3*(diff(diff(f(x, t), x), x))^2-4*(diff(diff(diff(f(x, t), x), x), x))*(diff(f(x, t), x))-(diff(f(x, t), x))*(diff(f(x, t), t)) = 0

(12)

pde2 := %

(diff(diff(diff(diff(f(x, t), x), x), x), x)+diff(diff(f(x, t), t), x))*f(x, t)+3*(diff(diff(f(x, t), x), x))^2-4*(diff(diff(diff(f(x, t), x), x), x))*(diff(f(x, t), x))-(diff(f(x, t), x))*(diff(f(x, t), t)) = 0

(13)

N = 1

N = 1

(14)

S := f(x, t) = a[0]+a[1]*exp(t*n[1]+x*k[1])

f(x, t) = a[0]+a[1]*exp(t*n[1]+x*k[1])

(15)

A := eval(pde2, S)

(a[1]*k[1]^4*exp(t*n[1]+x*k[1])+a[1]*n[1]*k[1]*exp(t*n[1]+x*k[1]))*(a[0]+a[1]*exp(t*n[1]+x*k[1]))-a[1]^2*k[1]^4*(exp(t*n[1]+x*k[1]))^2-a[1]^2*k[1]*(exp(t*n[1]+x*k[1]))^2*n[1] = 0

(16)

simplify((a[1]*k[1]^4*exp(t*n[1]+x*k[1])+a[1]*n[1]*k[1]*exp(t*n[1]+x*k[1]))*(a[0]+a[1]*exp(t*n[1]+x*k[1]))-a[1]^2*k[1]^4*(exp(t*n[1]+x*k[1]))^2-a[1]^2*k[1]*(exp(t*n[1]+x*k[1]))^2*n[1] = 0)

a[0]*a[1]*exp(t*n[1]+x*k[1])*k[1]*(k[1]^3+n[1]) = 0

(17)

%/exp(t*n[1]+x*k[1])

(k[1]^3+n[1])*k[1]*a[1]*a[0] = 0

(18)

PPP := %

(k[1]^3+n[1])*k[1]*a[1]*a[0] = 0

(19)

Co := solve(PPP, {a[0], a[1], k[1], n[1]})

{a[0] = a[0], a[1] = a[1], k[1] = k[1], n[1] = -k[1]^3}, {a[0] = a[0], a[1] = a[1], k[1] = 0, n[1] = n[1]}, {a[0] = a[0], a[1] = 0, k[1] = k[1], n[1] = n[1]}, {a[0] = 0, a[1] = a[1], k[1] = k[1], n[1] = n[1]}

(20)

case1 := Co[1]

{a[0] = a[0], a[1] = a[1], k[1] = k[1], n[1] = -k[1]^3}

(21)

F := subs(case1, S)

f(x, t) = a[0]+a[1]*exp(-t*k[1]^3+x*k[1])

(22)

F1 := eval(Y, F)

u(x, t) = 2*a[1]*k[1]^2*exp(-t*k[1]^3+x*k[1])/(a[0]+a[1]*exp(-t*k[1]^3+x*k[1]))-2*a[1]^2*k[1]^2*(exp(-t*k[1]^3+x*k[1]))^2/(a[0]+a[1]*exp(-t*k[1]^3+x*k[1]))^2

(23)

pdetest(F1, pde)

0

(24)

N = 2

N = 2

(25)

S2 := f(x, t) = a[0]+a[1]*exp(t*n[1]+x*k[1])+a[2]*exp(t*n[2]+x*k[2])+a[3]*exp(t*n[1]+t*n[2]+x*k[1]+x*k[2])

f(x, t) = a[0]+a[1]*exp(t*n[1]+x*k[1])+a[2]*exp(t*n[2]+x*k[2])+a[3]*exp(t*n[1]+t*n[2]+x*k[1]+x*k[2])

(26)

eq5 := normal(eval(pde2, S2))

exp(t*n[1]+x*k[1])*a[0]*a[1]*k[1]^4-4*exp(t*n[1]+x*k[1])*exp(t*n[2]+x*k[2])*a[1]*a[2]*k[1]^3*k[2]+6*exp(t*n[1]+x*k[1])*exp(t*n[2]+x*k[2])*a[1]*a[2]*k[1]^2*k[2]^2-4*exp(t*n[1]+x*k[1])*exp(t*n[2]+x*k[2])*a[1]*a[2]*k[1]*k[2]^3+exp(t*n[1]+x*k[1])*exp(t*n[2]+x*k[2])*a[1]*a[2]*k[1]*n[1]-exp(t*n[1]+x*k[1])*exp(t*n[2]+x*k[2])*a[1]*a[2]*k[1]*n[2]-exp(t*n[1]+x*k[1])*exp(t*n[2]+x*k[2])*a[1]*a[2]*k[2]*n[1]+exp(t*n[1]+x*k[1])*exp(t*n[2]+x*k[2])*a[1]*a[2]*k[2]*n[2]+exp(t*n[1]+x*k[1])*exp(t*n[1]+t*n[2]+x*k[1]+x*k[2])*a[1]*a[3]*k[2]*n[2]+exp(t*n[2]+x*k[2])*exp(t*n[1]+t*n[2]+x*k[1]+x*k[2])*a[2]*a[3]*k[1]*n[1]+exp(t*n[1]+x*k[1])*a[0]*a[1]*k[1]*n[1]+exp(t*n[2]+x*k[2])*a[0]*a[2]*k[2]^4+exp(t*n[1]+t*n[2]+x*k[1]+x*k[2])*a[0]*a[3]*k[1]^4+exp(t*n[1]+t*n[2]+x*k[1]+x*k[2])*a[0]*a[3]*k[2]^4+exp(t*n[1]+x*k[1])*exp(t*n[2]+x*k[2])*a[1]*a[2]*k[1]^4+exp(t*n[1]+x*k[1])*exp(t*n[2]+x*k[2])*a[1]*a[2]*k[2]^4+exp(t*n[1]+x*k[1])*exp(t*n[1]+t*n[2]+x*k[1]+x*k[2])*a[1]*a[3]*k[2]^4+exp(t*n[2]+x*k[2])*exp(t*n[1]+t*n[2]+x*k[1]+x*k[2])*a[2]*a[3]*k[1]^4+4*exp(t*n[1]+t*n[2]+x*k[1]+x*k[2])*a[0]*a[3]*k[1]^3*k[2]+6*exp(t*n[1]+t*n[2]+x*k[1]+x*k[2])*a[0]*a[3]*k[1]^2*k[2]^2+4*exp(t*n[1]+t*n[2]+x*k[1]+x*k[2])*a[0]*a[3]*k[1]*k[2]^3+exp(t*n[2]+x*k[2])*a[0]*a[2]*k[2]*n[2]+exp(t*n[1]+t*n[2]+x*k[1]+x*k[2])*a[0]*a[3]*k[1]*n[1]+exp(t*n[1]+t*n[2]+x*k[1]+x*k[2])*a[0]*a[3]*k[1]*n[2]+exp(t*n[1]+t*n[2]+x*k[1]+x*k[2])*a[0]*a[3]*k[2]*n[1]+exp(t*n[1]+t*n[2]+x*k[1]+x*k[2])*a[0]*a[3]*k[2]*n[2] = 0

(27)

indets(eq5)

{t, x, a[0], a[1], a[2], a[3], k[1], k[2], n[1], n[2], exp(t*n[1]+x*k[1]), exp(t*n[2]+x*k[2]), exp(t*n[1]+t*n[2]+x*k[1]+x*k[2])}

(28)

eq6 := eval(eq5, {t*n[1]+x*k[1] = X, t*n[2]+x*k[2] = Y}); indets(eq6)

Error, invalid input: exp expects its 1st argument, x, to be of type algebraic, but received u(x,t) = 2*diff(diff(f(x,t),x),x)/f(x,t)-2*diff(f(x,t),x)^2/f(x,t)^2

 

{eq6}

(29)

``

NULL

NULL

NULL

NULL

S3 := f(x, t) = a[0]+sum(exp(t*n[i]+x*k[i]), i = 1 .. 3)+a[1]*exp(t*n[1]+t*n[2]+x*k[1]+x*k[2])+a[2]*exp(t*n[1]+t*n[3]+x*k[1]+x*k[3])+a[3]*exp(t*n[2]+t*n[3]+x*k[2]+x*k[3])+a[4]*exp(t*n[1]+t*n[2]+t*n[3]+x*k[1]+x*k[2]+x*k[3])

f(x, t) = a[0]+exp(t*n[1]+x*k[1])+exp(t*n[2]+x*k[2])+exp(t*n[3]+x*k[3])+a[1]*exp(t*n[1]+t*n[2]+x*k[1]+x*k[2])+a[2]*exp(t*n[1]+t*n[3]+x*k[1]+x*k[3])+a[3]*exp(t*n[2]+t*n[3]+x*k[2]+x*k[3])+a[4]*exp(t*n[1]+t*n[2]+t*n[3]+x*k[1]+x*k[2]+x*k[3])

(30)

NULL

NULL

eq5 := normal(eval(pde2, S3))

 

``

Download N-soliton.mw

the most paper use another function to get the result and then do substitute i try to get by the way of them but i fail so how about if we can get the results in direct function there is any way for finding thus parameter after substitution of our function in ode?

restart

with(PDEtools)

with(LinearAlgebra)

NULL

with(SolveTools)

undeclare(prime)

`There is no more prime differentiation variable; all derivatives will be displayed as indexed functions`

(1)

"          with(Student[ODEs][Solve]):"

_local(gamma)

Warning, A new binding for the name `gamma` has been created. The global instance of this name is still accessible using the :- prefix, :-`gamma`.  See ?protect for details.

 

ode := beta*U(xi)^2*c^2+(-alpha*c^2+1)*U(xi)+mu^2*c^2*(diff(diff(U(xi), xi), xi)) = 0

beta*U(xi)^2*c^2+(-alpha*c^2+1)*U(xi)+mu^2*c^2*(diff(diff(U(xi), xi), xi)) = 0

(2)

n := 2

2

(3)

F := U(xi) = sum(tanh(xi)^(i-1)*(B[i]*sech(xi)+A[i]*tanh(xi)), i = 1 .. n)+A[0]

U(xi) = B[1]*sech(xi)+A[1]*tanh(xi)+tanh(xi)*(B[2]*sech(xi)+A[2]*tanh(xi))+A[0]

(4)

K1 := eval(ode, F)

beta*(B[1]*sech(xi)+A[1]*tanh(xi)+tanh(xi)*(B[2]*sech(xi)+A[2]*tanh(xi))+A[0])^2*c^2+(-alpha*c^2+1)*(B[1]*sech(xi)+A[1]*tanh(xi)+tanh(xi)*(B[2]*sech(xi)+A[2]*tanh(xi))+A[0])+mu^2*c^2*(B[1]*sech(xi)*tanh(xi)^2-B[1]*sech(xi)*(1-tanh(xi)^2)-2*A[1]*tanh(xi)*(1-tanh(xi)^2)-2*tanh(xi)*(1-tanh(xi)^2)*(B[2]*sech(xi)+A[2]*tanh(xi))+2*(1-tanh(xi)^2)*(-sech(xi)*tanh(xi)*B[2]+A[2]*(1-tanh(xi)^2))+tanh(xi)*(sech(xi)*tanh(xi)^2*B[2]-sech(xi)*(1-tanh(xi)^2)*B[2]-2*A[2]*tanh(xi)*(1-tanh(xi)^2))) = 0

(5)

solve(identity(K1, {xi}), {A[0], A[1], A[2], B[1], B[2]})

Error, (in unknown) incorrect use of identity(<expr>,<name>)

 

Download Find_params.mw

i try to get same result by substituation but i don't know what is mistake after i take second derivative is wronge i don't know how get same result as in paper did can anyone help  to calculate this part is not hard but is complicated ,How calculated second derivative and put in our ode to get the parameters?

restart

with(PDEtools)

with(LinearAlgebra)

NULL

with(SolveTools)

undeclare(prime)

`There is no more prime differentiation variable; all derivatives will be displayed as indexed functions`

(1)

"          with(Student[ODEs][Solve]):"

_local(gamma)

declare(Omega(x, y, t)); declare(U(xi)); declare(u(x, y, t)); declare(Q(xi)); declare(V(xi)); declare(W(xi)); declare(f(xi))

Omega(x, y, t)*`will now be displayed as`*Omega

 

U(xi)*`will now be displayed as`*U

 

u(x, y, t)*`will now be displayed as`*u

 

Q(xi)*`will now be displayed as`*Q

 

V(xi)*`will now be displayed as`*V

 

W(xi)*`will now be displayed as`*W

 

f(xi)*`will now be displayed as`*f

(2)

NULL

ode := -delta*(diff(diff(U(xi), xi), xi))+U(xi)*(w^2-gamma*U(xi)-beta-alpha) = 0

-delta*(diff(diff(U(xi), xi), xi))+U(xi)*(w^2-gamma*U(xi)-beta-alpha) = 0

(3)

ode1 := -delta*(diff(diff(f(xi), xi), xi))+f(xi)*(w^2-gamma*f(xi)-beta-alpha) = 0

-delta*(diff(diff(f(xi), xi), xi))+f(xi)*(w^2-gamma*f(xi)-beta-alpha) = 0

(4)

F := U(xi) = sum(tanh(xi)^(i-1)*(B[i]*sech(xi)+A[i]*tanh(xi)), i = 1 .. n)+A[0]

U(xi) = sum(tanh(xi)^(i-1)*(B[i]*sech(xi)+A[i]*tanh(xi)), i = 1 .. n)+A[0]

(5)

S := U(f(xi)) = sum(cos(f(xi))^(i-1)*(B[i]*sin(f(xi))+A[i]*cos(f(xi))), i = 1 .. n)+A[0]

U(f(xi)) = sum(cos(f(xi))^(i-1)*(B[i]*sin(f(xi))+A[i]*cos(f(xi))), i = 1 .. n)+A[0]

(6)

``

n := 2

2

(7)

eval(ode1, S)

-delta*(diff(diff(f(xi), xi), xi))+f(xi)*(w^2-gamma*f(xi)-beta-alpha) = 0

(8)

Download complex-issue.mw

1 2 3 4 5 6 7 Last Page 1 of 16